Nature of science questionnaire for students, Indonesian version: factor analysis, reliability and validity. (June 2020) - Santiani,; Purwantoyo, E; Wiyanto, W; Ridho, S; Iswari, R S; Marwoto, P; Rusilowati, A; Sudarmin, S; Ngabekti, S
Abstract: There are already many questionnaires on the nature of science that are used in general, but it is still very rare for Indonesian version. This study developed an Indonesian version of questionnaire on the nature of science for students. The questionnaire consists of 27 items with nine dimensions as result of literature study. The questionnaire was validated by 12 experts with improvements to several items. Questionnaire is reliable with 11 items are valid. Factor analysis shows that this questionnaire consists of ten dimensions that is not in accordance with the grid arranged. Excess dimensions of factor analysis occur because these dimensions are closely interrelated so that their indicators are difficult to differentiate. This tested questionnaire can be used to see the students' views on the nature of science. To compile the next questionnaire on the nature of science, we recommend that the dimensions be simplified; the dimensions that are closely related should be made into one.